Religionsdidaktik für Religionslose - Woppowa, Jan; Käbisch, David (Religionsunterricht weiterdenken. Innovative Ansätze für eine zukunftsfähige Religionsdidaktik)

Enhancing Comprehension and Navigation in Jupyter Notebooks with Static Analysis - Shivarpatna Venkatesh, Ashwin Prasad; Wang, Jiawei; Li, Li; Bodden, Eric
Jupyter notebooks enable developers to interleave code snippets with rich-text and in-line visualizations. Data scientists use Jupyter notebook as the de-facto standard for creating and sharing machine-learning based solutions, primarily written in Python. Recent studies have demonstrated, however, that a large portion of Jupyter notebooks available on public platforms are undocumented and lacks a narrative structure. This reduces the readability of these notebooks. To address this shortcoming, this paper presents HeaderGen, a novel tool-based approach that automatically annotates code cells with categorical markdown headers based on a taxonomy of machine-learning operations, and classifies and displays function calls according to this taxonomy. For this functionality to be realized, HeaderGen enhances an existing call graph analysis in PyCG. To improve precision, HeaderGen extends PyCG's analysis with support for handling external library code and flow-sensitivity. The former is realized by facilitating the resolution of function return-types. Furthermore, HeaderGen uses type information to perform pattern matching on code syntax to annotate code cells. The evaluation on 15 real-world Jupyter notebooks from Kaggle shows that HeaderGen's underlying call graph analysis yields high accuracy (96.4% precision and 95.9% recall). This is because HeaderGen can resolve return-types of external libraries where existing type inference tools such as pytype (by Google), pyright (by Microsoft), and Jedi fall short. The header generation has a precision of 82.2% and a recall rate of 96.8% with regard to headers created manually by experts. In a user study, HeaderGen helps participants finish comprehension and navigation tasks faster. All participants clearly perceive HeaderGen as useful to their task.
Keywords: static analysis; python; code comprehension; annotation; literate programming; jupyter notebook

Two Sparsification Strategies for Accelerating Demand-Driven Pointer Analysis - Karakaya, Kadiray; Bodden, Eric (2023 IEEE Conference on Software Testing, Verification and Validation (ICST))

Model Generation For Java Frameworks - Luo, Linghui; Piskachev, Goran; Krishnamurthy, Ranjith; Dolby, Julian; Schäf, Martin; Bodden, Eric (IEEE International Conference on Software Testing, Verification and Validation (ICST))

Prophetologie – Eine Annäherung - Ghaffar, Zishan (Prophetie in Tenach, Bibel und Qur'an)

Performance management and work engagement – New evidence using longitudinal data - Ehmann, Stefanie; Kampkötter, Patrick; Maier, Patrick; Yang, Philip (Management Accounting Research)

Exploring the impact of specialist and generalist stars on organizational performance - Nalbantis, Georgios; Manger, Christian; Pawlowski, Tim; Yang, Philip (SSRN Electronic Journal)

Extreme Bootlegging: Individual-level Antecedents to Creative Deviance - Tenzer, Helene; Yang, Philip (Corporate Underground: Bootleg Innovation and Constructive Deviance)

Investigation of Different Load Characteristics, Component Dimensioning, and System Scaling for the Optimized Design of a Hybrid Hydrogen-Based PV Energy System - Möller, Marius Claus; Krauter, Stefan (Hydrogen)
The realization of a carbon-neutral civilization, which has been set as a goal for the coming decades, goes directly hand-in-hand with the need for an energy system based on renewable energies (REs). Due to the strong weather-related, daily, and seasonal fluctuations in supply of REs, suitable energy storage devices must be included for such energy systems. For this purpose, an energy system model featuring hybrid energy storage consisting of a hydrogen unit (for long-term storage) and a lithium-ion storage device (for short-term storage) was developed. With a proper design, such a system can ensure a year-round energy supply by using electricity generated by photovoltaics (PVs). In the energy system that was investigated, hydrogen (H2) was produced by using an electrolyser (ELY) with a PV surplus during the summer months and then stored in an H2 tank. During the winter, due to the lack of PV power, the H2 is converted back into electricity and heat by a fuel cell (FC). While the components of such a system are expensive, a resource- and cost-efficient layout is important. For this purpose, a Matlab/Simulink model that enabled an energy balance analysis and a component lifetime forecast was developed. With this model, the results of extensive parameter studies allowed an optimized system layout to be created for specific applications. The parameter studies covered different focal points. Several ELY and FC layouts, different load characteristics, different system scales, different weather conditions, and different load levels—especially in winter with variations in heating demand—were investigated.

Multiple Team Membership Arrangements: Putting the Worker Front and Center - Moore, Ozias; Rapp, Tammy L.; Mistry, Sal; Bell, Bradford S.; Grossman, Rebecca; Miller, Jack; Finuf, Kayla D.; Sackett, Esther; Mayo, Anna; Tenzer, Helene; Yang, Philip; Hoegl, Martin; et al. (Academy of Management Proceedings)

Performance management and work engagement – New evidence using longitudinal data - Ehmann, Stefanie; Kampkötter, Patrick; Maier, Patrick; Yang, Philip (Management Accounting Research)

Zermelo navigation problems on surfaces of revolution and geometric optimal control - Bonnard, Bernard; Cots, Olivier; Wembe, Boris (ESAIM: Control, Optimisation and Calculus of Variations)
In this article, the historical study from Carathéodory-Zermelo about computing the quickest nautical path is generalized to Zermelo navigation problems on surfaces of revolution, in the frame of geometric optimal control. Using the Maximum Principle, we present two methods dedicated to analyzing the geodesic flow and to compute the conjugate and cut loci. We apply these calculations to investigate case studies related to applications in hydrodynamics, space mechanics and geometry.

Schule spielen - die Ausbildung von Lehrkräften mithilfe von und als Simulation - Reis, Oliver; Büttner, Gerhard (Religion lernen. Jahrbuch für konstruktivistische Religionsdidaktik)

Wenn Gemeindeteams "Leitung" übernehmen. Die transformative Kraft von Gemeindeteams in den Netzwerkstrukturen im pastoralen Raum - Modellraum 4 - Reis, Oliver; Hofmeister, Lisa; Burke, Rebekka

How children co-construct a religious abstract concept with their caregivers: Theological models in dialogue with linguistic semantics - Reis, Oliver; Viertel, Franziska (religions)

Was ist das "Katholische" einer Schule? Drei Zugänge auf zukünftige Herausforderungen - Reis, Oliver; Hoyer, Isabelle (Kirche und Schule. Die Fachzeitschrift der Hauptabteilung Schule und Erziehung)

Religion Lernen. Jahrbuch für konstruktivistische Religionspädagogik

Wie sich als Verband zum Religionsunterricht positionieren - Reis, Oliver; Mellentin, Franziska; Theis, Joachim; Tomberg, Markus; Wedding, Michael (Katechetische Blätter)

Modellprojekt Entwicklung der ehrenamtlichen Mitverantwortung. Projektbericht 2: Wenn Gemeindeteams "Leitung" übernehmen - Reis, Oliver; Kolk, Matthias

Die Kunst des Störens - eine komplexe Rekonstruktion pragmatischer Rahmungen - Reis, Oliver; Maurer, Kristina (Religion lernen. Jahrbuch für konstruktivistische Religionsdidaktik)